1992
DOI: 10.1093/oxfordjournals.humrep.a137841
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin glue for reanastomosis of the Fallopian tube in the rabbit: adhesions and fertility

Abstract: Fertility and adhesions were examined in 41 rabbits in three treatment groups following the construction of microsurgical anastomoses with fibrin glue and by conventional suturing techniques. The three types of treatment were: isthmic anastomoses without resection, ampullary anastomoses, isthmic anastomoses following resection of oviduct segments. There were no significant differences between the two methods of performing the anastomoses in any of the three groups with respect to number of ovulations, number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…This concurs with the morphological studies comparing FG and sutured rabbit Fallopian tubes in other studies [31,81]. However, the authors concluded that FG anastomoses with differing luminal diameters (e.g., isthmic-ampullary) are best performed with an intraluminal stent to reduce the risk of stulas, adhesions, and stenosis resulting from poor stump approximation [168,170,171]. In a study comparing AFG, Tisseel (commercial), polyglycolic acid suture anastomoses and nonoperated rabbit oviducts, Weis-Fogh et al [86] found no adhesions in the 22 AFG anastomoses.…”
Section: Uterine Horn/ Fallopian Tube Anastomosessupporting
confidence: 85%
See 1 more Smart Citation
“…This concurs with the morphological studies comparing FG and sutured rabbit Fallopian tubes in other studies [31,81]. However, the authors concluded that FG anastomoses with differing luminal diameters (e.g., isthmic-ampullary) are best performed with an intraluminal stent to reduce the risk of stulas, adhesions, and stenosis resulting from poor stump approximation [168,170,171]. In a study comparing AFG, Tisseel (commercial), polyglycolic acid suture anastomoses and nonoperated rabbit oviducts, Weis-Fogh et al [86] found no adhesions in the 22 AFG anastomoses.…”
Section: Uterine Horn/ Fallopian Tube Anastomosessupporting
confidence: 85%
“…All anastomoses were patent, and scanning electron microscopy revealed abundant microvilli on the anastomotic cells. Gauwerky et al [168][169][170][171] also compared fertility following reduced suture FG, and sutured ampullary and isthmic anastomoses. Neither the FG nor the sutured anastomoses demonstrated signi cant group advantages regarding the number of ovulations, number of implantations, pregnancy rate, or nidation index ([live fetuses + dead fetuses/total number of corpora lutea] £ 100).…”
Section: Uterine Horn/ Fallopian Tube Anastomosesmentioning
confidence: 99%
“…The literature well documents the superiority of tubal reconstruction versus ART or IVF; however, there is no therapy, surgical or otherwise, established presently to restore tube length [14][15][16][17][18][19][20][21].…”
Section: Tubal Factor Infertilitymentioning
confidence: 99%
“…In tubal anastomosis animal models, the use of fibrin sealant was demonstrated to be as effective as microsurgi cal suturing in terms of postoperative fertility rates and epithelial morphology [16,17]. However, the issue of postoperative adhesion formation was not adequately ad dressed in the above studies; there appears to be similar [17] or higher [16] adhesion formation on the fibrin gluecovered compared to microsurgically sutured anasto moses.…”
Section: Discussionmentioning
confidence: 99%
“…However, the issue of postoperative adhesion formation was not adequately ad dressed in the above studies; there appears to be similar [17] or higher [16] adhesion formation on the fibrin gluecovered compared to microsurgically sutured anasto moses. In one clinical study, Tulandi [ 18] reported no dif- Nidation index = Number of embryos divided by corpora lutea on ipsilateral ovary.…”
Section: Discussionmentioning
confidence: 99%